A Stylistic Analysis of Figurative Language and its Functions in the Four (Deluxe) Album by One Direction - Sa'idah, Na'imatus; Permatasari, Riana (Universitas PGRI Semarang, 2024)
This research belongs to qualitative research that analyzed the types and the functions of figurative language in the Four (Deluxe) album using theory of Johnson and Arp. This research used the primary data taken from the song lyrics in the album and the secondary data were obtained from articles, journals, and previous studies related to the research topic. The data collection technique was done by listening to songs, reading the lyrics, identifying the data and classifying the data into the types of figurative language and the functions of figurative language in the album. After collecting the data, the researchers analyzed the data based on the research questions. From the results of the research, the researchers concluded that types of figurative language found in the album is hyperbole, simile, symbolic, personification, and allegory. Meanwhile, the functions of figurative language found in the album were to provide imaginative pleasure, to talk a lot in a short compass, and to add emotional intensity. Hyperbole was the most frequent used figurative language (5 data), and to provide imaginative pleasure was the most frequent found function in the album (9 data). These two results were interconnected because hyperbole describing something in exaggerated terms that can make the reader interpret the meaning of the lyrics and make the reader use their imaginations.